An insight to strategical responses of particulate pollution in plants: From phenome to genome - Soumya Chatterjee; Mamun Mandal; Mrinalini Kakkar; Ganapati Basak; Nasrin Banu Khan; Ranadhir Chakraborty; Robert Popek; Abhijit Sarkar; Chandan Barman (Plant Stress)
Particulate matter (PM) is an extremely overlooked air pollutant with drastic effects on the biome, owing to the industrial and agricultural advancements, significantly exacerbating global environmental contamination levels. The altered atmosphere in urban settings due to PM pollution profoundly influences plants' morphological, physiochemical state and allied responses. PM exposure leads to drastic decrease in plant-height, phytomass, leaf number, leaf length and productivity. PM change the epicuticular wax patterns, penetrates plant tissue through stomata, and denatures the chloroplast pigmentation. It changes leaves' light absorption and reflection patterns, weakening the total radiation that reaches the chlorophyll antenna and ultimately reducing the photosynthetic rate and electron transport chain. Consequently, this alters plants morphology like wax deposits, thick epidermis, and long trichomes near stomata. Moreover, PM stress also adversely effects gluconeogenesis, amino acid biosynthesis, TCA cycle, and photorespiration-associated gene expression. Several transcription factors, such as MYB, C3H, and G2-homologues, are activated as a collective stress response. Additionally, ascorbic acid, proline and soluble sugars accumulate and several antioxidants are produced to scavenge the PM-induced reactive oxygen species (ROS). This review aims to document plants' various responses to PM pollution in their respective eco-geographic settings and investigate ways used by plants to mitigate PM pollution. We also enumerate the consequences of PM pollution on plants and the corresponding phenomic and genetic mechanisms through which plants adapt.